Evaluation of Elastic Settlement Behavior in Small-Strain Range of Cement-Treated Clayey Soil - Muhammad Akmal Putera; Noriyuki Yasufuku; Adel Alowaisy; Ryohei Ishikura; Jumana G. Hussary; Ahmad Rifa’i (International Association of Lowland Technology, 2022)
Indonesia is developing high-speed railway lines that are expected to connect the major cities. Along the railway, the lowland area is mainly comprised of clayey soil characterized by a high compressibility index and high water content, which causes soil settlement in the long term. Therefore, to reduce the potential of settlement, choosing a suitable railway structure, such as the ballastless track, is essential. Despite the track structure, the subsoil mechanical properties often require improvement to limit the railways’ settlement. Using cement-treated soil, a combination technique was provided to protect the shallow ground and the ballastless track, effectively reducing the stress distribution during construction periods and maintaining low construction costs for developing countries. To assure longer serviceability, there is a high need for an accurate evaluation of the elastic settlement subjected to train loading. Therefore, this paper proposes an elastic settlement prediction model for cement-treated soils considering the curing period, cement content, and confining pressure within the small-strain ranges. The model optimizes the mixing ratio at a specific curing period, reflecting the wheel-base loading on the cement-treated soil layer. Moreover, a simple power formula to determine the initial mechanical properties of the cement-treated soils was proposed.